Harnessing adaptive capacity to close the pandora's box of open innovation. Issue 3 (15th March 2020) - Mahdad, Maral; De Marco, Chiara Eleonora; Piccaluga, Andrea; Di Minin, Alberto
ABSTRACT: This paper focuses on how companies deploy structural properties of adaptive capacity ( multiplexity, redundancy and loose coupling ) to cope with the phenomenon of internal challenges of Open Innovation (OI) implementation, i.e. organisational and cultural changes. We developed a single case study, which offered significant findings. First, the multiplexity of relationships in OI settings helps to face the challenges of organisational and cultural changes by triggering trust formation and interaction. Second, redundancy has twofold elements: institutional logics redundancy triggers cultural change challenges which can be overcome through management practices and communications; task redundancy facilitates knowledge sharing and collaboration, thus helping to deal with organisational change challenges. Finally, loose coupling in OI settings facilitates social interconnectedness among members through management practices, helping to face organisational and cultural change challenges. We provide managerial and theoretical implication to deal with the challenges of OI in relation to both organisational and cultural changes.